Influence of Overpressure Breathing on Vowel Formant Frequencies - VOJNOVIĆ, Milan; MIJIĆ, Miomir; ŠUMARAC PAVLOVIĆ, Dragana; VOJNOVIĆ, Nebojša (Archives of Acoustics, 2021)
Voice controlled management systems are based on speech recognition techniques. The use of such systems in combat aircraft is complex due to a number of critical factors which affect the accuracy of speech recognition, such as high level of ambient noise and vibration, use of oxygen masks, serious psycho-physical stress of speakers, etc. One of the specificity of the oxygen mask application is overpressure breathing. The results of the simulations presented in this paper show that the presence of overpressure on the order of 1000 Pa in the vocal tract has a significant influence on the first two formant frequencies. The formants discrimination field is significantly reduced when oxygen mask is used, influencing both perceptive and automatic discrimination of spoken vowels.